Rotational Presidency in Nigeria: Issues and Reality: International Journal of Social Sciences. 7 (2) - Tom, Edet; Attai, Amadu (Afrischolar Discovery Repository (Annex), 2024)
Visit https://afrischolarrepository.net.ng for more publications.